Improving Management with Individual and Group-Based Consulting : Results from a Randomized Experiment in Colombia - Iacovone, Leonardo; Maloney, William; McKenzie, David (World Bank, Washington, DC, 2019)
Differences in management quality are an important contributor to productivity differences across countries. A key question is how to best improve poor management in developing countries. This paper tests two different approaches to improving management in Colombian auto parts firms. The first uses intensive and expensive one-on-one consulting, while the second draws on agricultural extension approaches to provide consulting to small groups of firms at approximately one-third of the cost of the individual approach. Both approaches lead to improvements in management practices of a similar magnitude (8-10 percentage points), so that the new group-based approach dominates on a cost-benefit basis. Moreover, the paper finds some evidence that the group-based intervention led to increases in firm size over the next three years, while the impacts on firm outcomes are smaller and statistically insignificant for the individual consulting. The results point to the potential of group-based approaches as a pathway to scaling up management improvements.